ROTUNDORO: A web-based decision support prototype for housing refurbishments considering consumer preferences. Issue 1 (1st September 2022) - Kaltenegger, J K; Ossokina, I V; Röck, M; Pauwels, P
Abstract: Insulation materials represent the first and most important improvement measure when refurbishing residential buildings. Materials, however, differ on a wide set of criteria (e.g. functional, environmental, economic). It remains difficult to find trade-offs between these criteria in collective decision-making processes about the choice of renovation materials. Together with energy collectives and construction engineers, homeowners hence seek to find solutions that balance engineering evaluation methods and consumer preferences. This problem is addressed by the platform ROTUNDORO, which introduces a prototype online platform for engineers to simulate the effects of different material choices considering multiple criteria. ROTUNDORO relies on Building Information Modelling (BIM) and Linked Building Data (LBD) to link material performances to building components, which are then assessed and visualised in design performance scenarios. To verify these design scenarios, their potential market adoption is visualised inside the platform to show the probability of acceptance by the homeowners. The calculation of this probability of acceptance is based on consumer research, backed by the results of a Stated Choice Experiment (SCE) conducted amongst 500 Dutch homeowners, to investigate preferred choices between insulation material packages. Our findings reveal a high willingness of the studied population to invest in energy refurbishment. Reducing CO2 emissions and noise levels as well as improving comfort is just as important as financial savings. 3 4 5